The SEC's 'Fair Value' Standard for Mutual Fund Investment in Restricted Shares and Other Illiquid Securities - Janet K. Smith; Richard L. Smith; Karyn L. Williams (Claremont McKenna College, Department of Economics, 2000)
Mutual funds generally do not invest in venture capital, private equity, or restricted shares of public companies. Consequently, individuals who desire to invest in such securities are unable to do so through diversified mutual funds. In this paper, we identify public policies and regulations that discourage mutual fund involvement in the markets for illiquid equity. We also present evidence that changes in SEC policy caused mutual funds to retreat from investing in illiquid equity. Under the Investment Company Act of l940, the SEC requires mutual fund boards to determine and report the "fair value" of their investments in restricted shares and other illiquid equity claims. The SEC interprets fair value to mean value in current sale. Under the Investment Company Act, fair value reporting is a "certification" standard that presumes investors rely on the value representations of the fund board and its auditors. We consider whether alternatives to certification and current sale valuation could reduce barriers to mutual fund investment, without exposing individuals who invest in mutual funds to excessive risk or potential manipulation. To assess the effects of public policies, we analyze recent efforts of the SEC to apply the fair-value standard and examine court decisions arising from subsequent litigation. We also analyze the financial economics literature concerning discounts for illiquidity and the implications for valuing restricted shares. The paper concludes with a discussion of policy alternatives, including allowing funds to rely more on "transparency" in lieu of certification and allowing funds more latitude in determining and reporting the values of their illiquid securities.
Keywords: 330